Perception of Health Care Professionals on Transplantation in the Treatment of COVID-19 Patients - Sah, Bikash; Jha, Shivendra; Ayer, Ashok; Raj Mishra, Deebya; N. Yadav, B. (International Journal of Global Health, 2020)
Corona virus disease 2019 (COVID-19) caused by severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) has rapidly evolved as a pandemic with a challenge to the entire world for its management. Various modalities of treatment have been tried till date and when all the modalities failed then the only option that has been shown to be successful in some cases is lung transplantation. Decision for Solid-organ transplantation is not only made based upon its therapeutic requirement but also need to be supported by the law of land. In this regard, current Nepalese law is not with the provision for lung transplantation.  Thus, in order to make the concerned authorities aware of it and also as a step toward the preparedness for COVID-19 pandemic, this research has been conducted with an aim to see the perception of health care professionals of tertiary care centre of eastern Nepal regarding the legal aspects of lung transplantation. Conclusion Outcome of this research has supported the therapeutic aspect of transplantation over its legal issue in the emergency conditions like COVID-19 Pandemic.
Keywords: COVID-19; Legal system; Lung Transplantation; Organ Transplantation; Pandemic.